Ruthenium(III) aqua-chloro complex chemistry : the interconversion of the hexachlororuthenate(III) and aquapentachlororuthenate(III) species - Viljoen, Karen (Stellenbosch : University of Stellenbosch, 2011)
Thesis (MSc)--University of Stellenbosch, 2003.